2008
DOI: 10.1080/00016480701387173
|View full text |Cite
|
Sign up to set email alerts
|

The effect of unilateral multichannel cochlear implant on bilaterally perceived tinnitus

Abstract: Seven patients (17%) reported the perception of a 'new tinnitus' after surgery. With the CI off tinnitus was abolished in 23 patients (56.1%) in the implanted ear and in 22 patients (53.6%) in the contralateral ear. With the CI on tinnitus was abolished in the ipsilateral ear in 27 patients (65.8%) and in the contralateral ear in 27 patients (65.8%). Statistical analysis showed a significant reduction of the total THI score and of each subscale score (p < 0.001).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
77
1
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(92 citation statements)
references
References 16 publications
8
77
1
6
Order By: Relevance
“…After that, several studies have confirmed these results, showing that suppression of tinnitus occurs in 15-95% of the cases [Rubinstein et al, 2003;Quaranta et al, 2008;Van de Heyning et al, 2008;Akdogan et al, 2009;Pan et al, 2009;Bovo et al, 2011;Kompis et al, 2012]. However, some cochlear implant patients have reported an exacerbation (1-10%) or the onset (0-23.5%) of tinnitus after implantation [Baguley and Atlas, 2007;Quaranta et al, 2008;Akdogan et al, 2009;Bovo et al, 2011;Kompis et al, 2012]. Other remarkable effects of unilateral cochlear implantation are the reduction of tinnitus in the contralateral ear and the existence of residual inhibition of tinnitus after switching off the cochlear implant [Baguley and Atlas, 2007;Quaranta et al, 2008].…”
Section: Introductionsupporting
confidence: 48%
See 2 more Smart Citations
“…After that, several studies have confirmed these results, showing that suppression of tinnitus occurs in 15-95% of the cases [Rubinstein et al, 2003;Quaranta et al, 2008;Van de Heyning et al, 2008;Akdogan et al, 2009;Pan et al, 2009;Bovo et al, 2011;Kompis et al, 2012]. However, some cochlear implant patients have reported an exacerbation (1-10%) or the onset (0-23.5%) of tinnitus after implantation [Baguley and Atlas, 2007;Quaranta et al, 2008;Akdogan et al, 2009;Bovo et al, 2011;Kompis et al, 2012]. Other remarkable effects of unilateral cochlear implantation are the reduction of tinnitus in the contralateral ear and the existence of residual inhibition of tinnitus after switching off the cochlear implant [Baguley and Atlas, 2007;Quaranta et al, 2008].…”
Section: Introductionsupporting
confidence: 48%
“…The first report of subjective tinnitus being suppressed by a cochlear implant was published by House [1976]. After that, several studies have confirmed these results, showing that suppression of tinnitus occurs in 15-95% of the cases [Rubinstein et al, 2003;Quaranta et al, 2008;Van de Heyning et al, 2008;Akdogan et al, 2009;Pan et al, 2009;Bovo et al, 2011;Kompis et al, 2012]. However, some cochlear implant patients have reported an exacerbation (1-10%) or the onset (0-23.5%) of tinnitus after implantation [Baguley and Atlas, 2007;Quaranta et al, 2008;Akdogan et al, 2009;Bovo et al, 2011;Kompis et al, 2012].…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…Because our patients were deaf before the CI surgery, changes in frequency and intensity of tinnitus could not be evaluated. Some previous studies used validated questionnaires to assess the tinnitus handicap in the implanted patients [Andersson et al, 2009;Miyamoto et al, 1997;Pan et al, 2009;Quaranta et al, 2008;Souliere Jr. et al, 1992]. However, data regarding tinnitus impairment before and after CI often include general information: better, no change or worse [Mo et al, 2002;Tyler, 1994].…”
Section: Discussionmentioning
confidence: 99%
“…Пионерская работа W. House [10], по-священная кохлеарной имплантации у человека, была опубликована через год. Кохлеарная имплантация стала стремительно развиваться, одноканальные электроды с достаточно ограниченными возможностями (по кодиров-ке сигнала, распознаванию речи), уступили место много-канальным электродам, которые доказали свою эффек-тивность в работах многих авторов [11][12][13][14][15].…”
unclassified